2020
DOI: 10.3390/ijms21228682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles (EVs) in the Epigenetic Regulation of Bone Metabolism and Osteoporosis

Abstract: Extracellular vesicles (EVs) are complex phospholipidic structures actively released by cells. EVs are recognized as powerful means of intercellular communication since they contain many signaling molecules (including lipids, proteins, and nucleic acids). In parallel, changes in epigenetic processes can lead to changes in gene function and finally lead to disease onset and progression. Recent breakthroughs have revealed the complex roles of non-coding RNAs (microRNAs (miRNAs) and long non-coding RNAs (lncRNAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 169 publications
(206 reference statements)
0
25
0
Order By: Relevance
“…Several studies reported that miRNAs could be transferred between cells via EVs [ 6 , 7 , 21 ]; thus, we wondered whether PC3-derived EVs could transfer miRNA Let-7b to THP-1 cells. We exposed THP-1 monocytic cells, after TPA differentiation into M0 macrophages, to 100 μg/mL PC3-EVs for different times and observed the appearance of red fluorescent EV-like particles in the cytoplasm after 30 min incubation ( Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that miRNAs could be transferred between cells via EVs [ 6 , 7 , 21 ]; thus, we wondered whether PC3-derived EVs could transfer miRNA Let-7b to THP-1 cells. We exposed THP-1 monocytic cells, after TPA differentiation into M0 macrophages, to 100 μg/mL PC3-EVs for different times and observed the appearance of red fluorescent EV-like particles in the cytoplasm after 30 min incubation ( Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, this would require a reorientation of healthcare systems to meet the challenge set forth by OP, ensuring adequate care, health promotion, and treatment equity and avoiding the fragmentation of the clinical route. Over time, different biomarkers have been proposed for OP, among which those most discussed are specific multifunctional proteins (e.g., Annexin A2 and prolyl 4-hydroxylase) and circulating miRNAs (e.g., miR-223-3p, miR-148a-3p, miR-125b-5p, and miR-124-3p) [ 16 , 54 , 55 ]. However, the information related to these biomarkers during OP are still limited due to the different types of samples (serum, circulating monocytes, bone marrow, and bone tissue) obtained from patients of different sexes and different ethnic groups with low BMD or bone fractures and compared with healthy or osteoarthritis patients [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent breakthroughs have highlighted different methods starting from noncoding RNAs [microRNAs (miRNAs) and long noncoding RNAs (lncRNAs)], proteins, enzymes, or hormones [ 15. , 16. , 17.…”
Section: Op Management In the Covid-19 Eramentioning
confidence: 99%
“…The majority of EV research has focused on miRNA, but other RNA species that can be found in EVs include messenger RNA (mRNA), long non-coding RNA (lncRNA), ribosomal RNA (rRNA), transfer RNA (tRNA), RNA repeats, and circular RNA (circRNA) [ 82 , 83 , 84 , 85 , 86 ]. EV cargo can also include DNA and other genetic materials that reflect their cellular origin [ 87 , 88 ].…”
Section: Factors Contributing To Paracrine Benefits Of Mscs and Its Evs In Ischemic Strokementioning
confidence: 99%